1960
DOI: 10.1097/00002060-196004000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Flow, Oxygen Uptake and Tissue Temperatures Produced by Therapeutic Physical Agents

Abstract: Although the use of ultrasound as a therapeutic agent in the field of physical medicine continues to grow, there are still a number of questions concerning its physiologic effects which remain unanswered. With regard to the thermal response, it is generally accepted that practically the entire amount of energy applied to the tissues through this medium is absorbed and converted into heat. As a result, there is a rise in tissue temperature, most marked in the bones and nerves in which selective heating appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1
3

Year Published

1966
1966
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 0 publications
1
32
1
3
Order By: Relevance
“…Similar studies involving only SWT that were conducted on either asymptomatic subjects (12,14,15,31) or patient groups (10,32,33) have been reported previously. However, to our knowledge this will be the first in vivo study that investigated the deep physiological responses to RF exposure below the shortwave frequency band.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar studies involving only SWT that were conducted on either asymptomatic subjects (12,14,15,31) or patient groups (10,32,33) have been reported previously. However, to our knowledge this will be the first in vivo study that investigated the deep physiological responses to RF exposure below the shortwave frequency band.…”
Section: Introductionsupporting
confidence: 62%
“…Increasing muscle blood flow may potentially aid faster recovery from post exercise fatigue. In physiotherapy, radiofrequency (RF)-based EPAs are among those that claim to increase blood flow as well as improve soft tissue compliance, mainly by inducing tissue hyperthermia (9)(10)(11)(12)(13)(14)(15). Measures relating to blood flow and tissue compliance closely reflect the body's response when tissues are exposed to heat, with the radiofrequency energy potentially capable of inducing a hyperthermic effect at depth (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…When considering that a major component in the management of musculoskeletal pain (or other diseaserelated symptoms) often involves the ability to control blood flow to the affected area, the present study suggests that static magnets do not have the same effect on blood flow as other therapeutic modalities. 1,3,5,18,21,28 Despite numerous anecdotal reports and an enormous increase in the usage of magnet therapy, 9 the current study suggests that an increase in blood flow may not be one of the mechanisms for the reduction in pain that has been associated with wearing static magnets. 32,33 Previous literature has indicated little effect of static magnets on nerve conduction velocity 14,33 and nerve excitation threshold.…”
Section: Discussionmentioning
confidence: 77%
“…The impact on blood flow of common therapeutic modalities such as ultrasound, 5,11,21,22,36 electrical stimulation, 18,24,28 massage, 25,27 hot and cold packs, 1,2,3,6,8,16 and microwave therapy 19 has been studied extensively. However, there are few investigations involving the effect of static magnets on animal 17,31 and human 4,23,26 blood flow, and none has produced compelling evidence that static magnets significantly alter blood flow.…”
mentioning
confidence: 99%
“…These results suggest that CRet could warm deep tissue more effectively than HP. HP is classified as superficial thermotherapy [10], and superficial heat modalities do not sufficiently raise the temperatures of deeper muscles [30]. Previous studies reported that HP did not increase the muscle flexibility and that short wave diathermy classified as deep thermotherapy, which is similar to CRet, was more effective for improving tissue extensibility than HP [31,32].…”
Section: Discussionmentioning
confidence: 99%